Enzyme-based biocatalysis for the treatment of organic pollutants and bioenergy production - Haque S.; Singh R.; Harakeh S.; Teklemariam A.D.; Alharthy S.A.; Tripathi S.C.; Singh R.P.; Aly Hassan A.; Srivastava N.; Gupta V.K. (My University, 2025)
Enzyme-based biocatalysis is emerging as an advanced technique to develop green processes that help to maintain the sustainability of the environment. The bioremediation of toxic organic pollutants and waste to bioenergy production using enzymes as biocatalysts is rapidly growing due to its eco-friendly and sustainable nature. Additionally, a range of microbial species that typically grow on organic wastes can be used to produce these enzymes in an efficient manner. This is seen as a potential strategy for the development of cost-effective manufacturing for a number of biotechnological applications. The present study discusses biocatalysis as a promising and sustainable method toward the bioremediation of hazardous organic pollutants as well as for bioenergy production, based on the immense potential of enzymes as biocatalysts. Emphasis has been placed on evaluating the critical elements that can enhance the production of enzymes used as biocatalysts, as well as their functional effectiveness and stability. © 2022 Elsevier B.V.